Development of hair dyeing teaching materials using peek a boo technique based on e-books - Riwayani, Rika; Arfiyadie, Aqilah Muthiah (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
This research is a type of Research and Development (R&D) research with the aim of conducting research, namely to find out: 1) the procedure for developing hair coloring teaching materials using the peek a boo technique based on e-books for UNM Cosmetology students. 2) The response of UNM cosmetology students to hair coloring teaching materials using the e-book-based peek a boo technique. This research uses the Research and Development (R&D) method which develops and produces products with the ADDIE development model. The teaching material developed is hair coloring using the e-book based peek a boo technique. The subjects of this study were 13 undergraduate students concentrating on cosmetology class of 2019, the Department of Family Welfare Education, Faculty of Engineering, Makassar State University. The data analysis technique used is descriptive quantitative. The results of this study are 1) The procedure for developing e- book-based teaching materials refers to the ADDIE development model, analysis of the needs of lecturers, students and learning. 2) Based due diligence by students on e-books of 93% with "Very Good" criteria for use in learning activities as a source of material. Student responses to e-book-based teaching materials were "very good" and overall the assessment of 13 undergraduate students concentrating on cosmetology class of 2019 showed that the hair coloring e-book using the peek a boo technique could be used in learning activities